The Influence of Audit Committee Chairman Characteristics on Auditor Choice - Rosa, Sherly Luthfia; Dwita, Sany; Hayati, Dian Indah (Wahana Riset Akuntansi, 2025)
Purpose – This study aims to examine the impact of audit committee chair characteristics on auditor choice in healthcare, infrastructure, and transportation & logistic companies listed on the Indonesian Stock Exchange (IDX) from 2021 to 2023.Design/methodology/approach – This research uses purposive sampling, resulting in 86 companies. The study utilizes from company annual reports were analyzed using logistic regression.Findings – The results show that the business education of the audit committee chairman has a positive effect on the choice of Big 4 auditors. Meanwhile, other characteristics such as gender, professional qualifications, work experience, and tenure of the audit committee chairman do not affect the choice of Big 4 auditors. Therefore, the results of this study indicate that the business education of the audit committee chairman is the most influential factor in the choice of Big 4 auditorsOriginality/value – Previous studies have overlooked the role of audit committee chairs, focusing instead on audit committees in general. As audit committee leadership matters more, research examining the impact of audit committee chair characteristics on auditor choice remains limited. This study provides contributions to the existing literature by offering a novel perspective on the role of audit committee chairs as corporate governance representatives in auditor choice decisions within emerging market.Research limitations/implications – Research on the impact of audit committee chair characteristics remains limited. Furthermore, this study also has several limitations, such as the measurement of auditor choice, which is only measured by Big 4 and Non-Big 4 audit firms, thereby limiting its ability to provide insight into auditor choice. Additionally, the measurement of gender is limited to physical appearance or individual gender, without considering and understanding the complexity of values and characteristics of femininity and masculinity. The results of this study provide a significant contribution to the existing literature on the impact of audit committee chair characteristics on auditor choice.